The music rhythm tour board game for rhythmic sight-reading - Denny, Robert; Chwen Jen, Chen (Inderscience Enterprises Ltd., 2025)
Board games are recognised for their positive impact on learning across various disciplines. Despite their benefits, there is a noticeable lack of focus on utilising board games within music education. This study examined the effects of the music rhythm tour board game on rhythmic sight-reading ability among music learners aged 13–18 who completed their theory of music grade one. The quasi-experimental design involved a pre-test, gameplay sessions, and post-test with 36 participants from a music learning centre. The Music Rhythmic Reading Test (MRRT) measured participants' rhythmic efficiency, focusing on note duration, timing, and tempo. Data analysis involved descriptive statistics and paired t-tests, revealing significant post-test improvements in rhythmic sight-reading. Additionally, the analysis showed decreased rhythmic errors post-intervention. The results highlight the effectiveness of the music rhythm tour board game in enhancing rhythmic sight-reading skills and promoting game-based interventions in music education.